Avaliação dos efeitos da exposição antenatal ao sulfato de magnésio em recém-nascidos prematuros - Dias, Hannah Iorio (2018)
Preterm birth is an important factor related to neonatal morbidity and mortality, and remains among the most common obstetric complications, despite studies aimed its prevention. Different treatments have been evaluated to improve the outcomes of these newborns. Among them, the use of antenatal magnesium sulfate (MgSO4) to reduce the risk of cerebral palsy and gross motor dysfunction in surviving infants, but some results about this use are controversial regarding effects and safety. The aim of this study was to evaluate the neonatal outcomes of premature infants less than 34 weeks of gestational age, due to antenatal exposure to magnesium sulfate. A retrospective cohort study with infants born from September 2014 to September 2016 was conducted in a Brazilian tertiary maternity hospital, reference for maternal and neonatal care. Peri-intraventricular haemorrhage (IVH) and other short-term neonatal outcomes (dependent variables) were compared between preterm infants exposed and not exposed to antenatal magnesium sulfate. Of 357 eligible infants, 191 (53.5%) were exposed; 34% indicated exclusively for fetal neuroprotection. Comparing the neonatal outcomes of the group exposed to magnesium sulfate versus non-exposed, were statistically significant: 5-minute Apgar score <7 (5.2% vs. 11.5%, 0.495 [0.191-0.941], p = 0.035), neonatal resuscitation (42.4% vs. 53%, 1.532 [1.008-2.329], p = 0.046), bone metabolic disease (11.5% vs. 19.3%, 0.545 [0.303-0.982], p = 0.043), necrotizing enterocolitis (0% vs. 4.2%, p <0.01) and neonatal infection (79.1% vs. 68.7 %, 1.722 [1.067-2.779], p=0.026). Thirty-six infants (9.4% in the MgSO4 exposed group versus 11.8% in the non-exposed group, 1.357 [0.676-2.723], p=0,390) died during the hospital stay. This study found that antepartum exposure to magnesium sulphate up to 34 weeks was associated with lower prevalence of some neonatal morbidities (low Apgar score, need for resuscitation, necrotizing enterocolitis, bone metabolic disease), and higher prevalence of infection, with no change in mortality, hypotonicity or IVH.